Assessment of Analgesic Efficacy of Bilateral Lumbar Erector Spinae Plane Block for Postoperative Pain following Lumbar Laminectomy: A Single-Blind, Randomized Clinical Trial - Seyed Amirreza Akhlagh; Arash Farbood; Mahsa Tahvili; Afshin Amini; Keyvan Eghbal; Naeimehossadat Asmarian; Mahsa Banifatemi; Seyed Ali Hosseini (Pain Research and Management)
Background. The erector spinae plane (ESP) block is a novel approach to minimizing postoperative pain. We investigated the efficacy and side effects of the ultrasonography-guided bilateral ESP block in reducing pain in the first 24 hours after lumbar laminectomy. Materials and Methods. We conducted a single-blind (statistical analyst and those responsible for recording patient information postoperation were unaware of the study groups) randomized clinical trial on 50 patients aged 18 to 65 with American Society of Anesthesiology (ASA) class I or II physical status scheduled for lumbar laminectomy surgery at Shahid Chamran Hospital, Shiraz, Iran. Patients were randomly allocated to the ESP block (26 participants) or control (24 participants) group. A bilateral ESP block was administered to patients in the first group before general anesthesia, which was provided identically to both groups. The postoperative time to the first request of analgesia, pain score, total opioid use, side effects, and patient satisfaction were compared between the groups. Results. Compared with the control group, patients in the ESP block group had significantly more postoperative pain relief in the first hour and until 24 hours P<0.05. The total opioid consumption was lower in the ESP block group P<0.001. However, the ESP block led to a higher rate of urinary retention P=0.008. Conclusion. The bilateral ESP block effectively reduces postoperative pain following lumbar laminectomy, minimizing the need for narcotics. Further research is needed to delineate ways to reduce urinary retention as its main complication. This trial is registered with IRCT20100127003213N6.